Implementasi Pembelajaran Loose Part dengan Kearifan Budaya Lokal di KB Mutiara Karanggondang - Rohmatun, Siti; Nofan Zulfahmi, Muhammad (Generasi Emas, 2024)
The introduction and utilization of local cultural wisdom from an early age are important for children's development, especially amidst challenges in early childhood education such as limited resources and lack of interest in formal learning. This study aimed to implement Loose Part learning with local wisdom at KB Mutiara Karanggondang. The results showed high levels of enthusiasm among children towards Loose Part play, demonstrating the potential of this approach in effectively facilitating early childhood development. Integrating local wisdom into learning not only enhances children's engagement but also strengthens their identity with local culture. This research also highlights the importance of culturally relevant teaching methods in the context of early childhood education, which not only enhances learning experiences but also enriches local values in their education. Thus, this study provides a substantial contribution to improving sustainable educational approaches. By combining pedagogical innovation and local cultural wisdom, early childhood education can become more relevant, enjoyable, and significantly beneficial for children's holistic development.